The Use of Multiplex PCR Reactions to Identification of Lactic Acid Bacteria of Dangke - Nurwilda Kaswi; Mochammad Hatta; Rizalinda Sjahril (Berkala Kedokteran, 2023)
Abstract: Lactic acid bacteria can be isolated from various types of milk including dairy products. Dangke is an Indonesian traditional cheese made by Enrekang community, South Sulawesi. This study aims to identify the lactic acid bacteria by multiplex PCR method which are isolated from dangke obtained from Enrekang Regency. This  type  of  research  used  descriptive research  with  laboratory  observation  methods was performed on 30 cups of dangke are obtained from the markets in 5 sub-districts producing dangke in Enrekang Regency: they are the sub-districts of Cendana, Enrekang, Anggeraja, Alla, and Baraka. The results showed that Lactobacillus acidophilus was the most identified (33.33%) compared to Lactobacillus plantarum (16.67%). Based on the results of the research that has been carried out, it can be concluded that the lactic acid bacteria have been identified in dangke samples obtained from several sub-districts producing dangke in Enrekang Regency are Lactobacillus acidophilus and Lactobacillus plantarum species. Thus, we suggest that this laboratory technique is used to confirm the various species of lactic acid bacteria so it can prove more rapid and exactly that dangke is the rich content of lactic acid bacteria as probiotic candidate.